Responder
The two rational expressions are:
1. \( \frac{x + 3}{(x + 9)(x + 2)} \)
2. \( \frac{-2x}{(x + 9)(x - 3)} \)
Both expressions are already in their simplest forms.
Solución
Certainly! Let's analyze and simplify the two rational expressions you've provided:
1. **First Expression:**
\[
\frac{x + 3}{x^{2} + 11x + 18}
\]
**Factor the Denominator:**
\[
x^{2} + 11x + 18 = (x + 9)(x + 2)
\]
**Simplified Form:**
\[
\frac{x + 3}{(x + 9)(x + 2)}
\]
**Check for Common Factors:**
- The numerator \( x + 3 \) does not factor further and does not share any common factors with the denominator. Therefore, the expression is already in its simplest form.
2. **Second Expression:**
\[
\frac{-2x}{x^{2} + 6x - 27}
\]
**Factor the Denominator:**
\[
x^{2} + 6x - 27 = (x + 9)(x - 3)
\]
**Simplified Form:**
\[
\frac{-2x}{(x + 9)(x - 3)}
\]
**Check for Common Factors:**
- The numerator \( -2x \) does not share any common factors with the denominator other than constants. The expression is already simplified.
---
### **Additional Operations (Optional)**
If you're interested in performing operations with these two expressions, here's how you can add them:
**Adding the Two Expressions:**
\[
\frac{x + 3}{(x + 9)(x + 2)} + \frac{-2x}{(x + 9)(x - 3)}
\]
**Find a Common Denominator:**
The common denominator is \( (x + 9)(x + 2)(x - 3) \).
**Express Each Fraction with the Common Denominator:**
\[
\frac{(x + 3)(x - 3)}{(x + 9)(x + 2)(x - 3)} + \frac{-2x(x + 2)}{(x + 9)(x + 2)(x - 3)}
\]
**Combine the Numerators:**
\[
\frac{(x + 3)(x - 3) - 2x(x + 2)}{(x + 9)(x + 2)(x - 3)}
\]
**Simplify the Numerator:**
\[
(x + 3)(x - 3) = x^2 - 9
\]
\[
-2x(x + 2) = -2x^2 - 4x
\]
\[
\text{Combined Numerator} = x^2 - 9 - 2x^2 - 4x = -x^2 - 4x - 9
\]
**Final Combined Expression:**
\[
\frac{-x^2 - 4x - 9}{(x + 9)(x + 2)(x - 3)}
\]
This combined expression represents the sum of the two original rational expressions.
---
### **Domain Considerations**
For both expressions, it's important to note the values of \( x \) that make the denominator zero, as these are excluded from the domain.
1. **First Expression:**
\[
(x + 9)(x + 2) = 0 \implies x = -9, -2
\]
- **Domain:** All real numbers except \( x = -9 \) and \( x = -2 \).
2. **Second Expression:**
\[
(x + 9)(x - 3) = 0 \implies x = -9, 3
\]
- **Domain:** All real numbers except \( x = -9 \) and \( x = 3 \).
3. **Combined Expression:**
\[
(x + 9)(x + 2)(x - 3) = 0 \implies x = -9, -2, 3
\]
- **Domain:** All real numbers except \( x = -9, -2, 3 \).
---
If you have a specific operation or question in mind regarding these expressions, feel free to provide more details!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución